Historical Development of Health Research Ethics in Nepal - Khanal, Pratik; Maharjan, Sajana; Ghimire, Namita; Karki, Khem Bahadur (Journal of Nepal Health Research Council, 2018)
Health research in Nepal initiated with a survey in malaria in 1952. The first regulatory body for health research was Nepal Medical Research Committee formed under Ministry of Health. Ethical Review Body is the first ethical review structure. Nepal Health Research Council is now an independent body to regulate health research in Nepal. Development of research ethics in Nepal is clearly evident with the development of ethical guidelines; functioning of Ethical Review Board; expansion of institutional review committees and initiation of online submission system. However, monitoring compliance with research ethics could be a challenge for the NHRC.